Environmental Impact Assessment of Scrap Tires in the West Bank - Wa’el, Fadwa; Zaghlool, Raid (My University, 2018)
Abstract Scrap tires are one of the most important environmental problems worldwide due to the annual dramatic increasing quantities, in which the world production of one billion frames, the Arab world's share of 170 million while Palestine's share of nearly 400,000 in the West Bank. Developed countries use the 3 R technique (Recycle, Reuse, and Reduce) to minimize the health and environmental concerns of the used tires. However, the traditional way to get rid of scrap tires in the third world countries including Palestine is either by burning/incinerating or dumping them in legal or illegal landfills. Both options are environmentally unfriendly. For instance, in the case of burning, carcinogenic compounds are emitted because of combustion of polycyclic aromatic hydrocarbons and dioxins, in addition to the carbon monoxide, nitrogen oxides and sulfur, which have direct and indirect effects on water, soil, air, and human. Thus, the motivation of our project is to reduce the toxic emissions and to benefit from the scrap tiers by recycling and reusing them properly. Hence, in the first part of our study, we will summarize the most important negative effects of these scrap tires on land, air, water resources, flora, and fauna live in the West Bank by conducting a full spectrum of environmental impact assessment (EIA). In the previous study, we collected some statistical data by visiting the environmental authority in Nablus and by distributing questionnaires with a sample of 100 to the tire shops to get some insights about the disposal methods in Palestine, especially the northern governorates of the West Bank. In addition, the preliminary literature review shows the possibility of proposing a shredding facility followed by a pyrolysis process, in which the latter decomposes the organics in the scrap tires into valuable products such as oil, char, and carbon black. Such a new proposal needs an urgent EIA report to get an approval from the Palestinian ministry of environment and make mitigation and mentoring plan clear on this project.